PHILOSOPHICAL-PSYCHOLOGICAL ANALYSIS OF FEATURE FILMS AS A METHOD OF DEVELOPING STUDENTS' ANALYTICAL ABILITIES (Psychology Travelogs, 2025)
The paper considers the philosophical and psychological analysis of films as an interactive method of an innovative approach to teaching social and humanitarian disciplines (psychology, philosophy, sociology) based on psychological constructivism. Psychological constructivism is defined here as a productive approach to learning and teaching, which can significantly stimulate creativity and innovation in students' educational activities. The philosophical and psychological analysis of films is presented as a complex analytical operation that involves dividing into components of content and form, highlighting certain moments, studying features, determining the place and functional role in the general system of the work, establishing the nature of interaction with its other parts. The focus is on the positive aspects of using the philosophical and psychological analysis of films: the development of mental abilities and broadening the horizons of the individual, encouraging self-knowledge, the development of critical thinking and analytical skills, and the emotional enrichment of the individual. Key aspects of philosophical and psychological analysis of films by students during their studies are highlighted: philosophical vision of the main ideas and concepts, psychological approach to the behavior of characters, perception of visual and verbal means of transmitting deep psychological meanings, contextual subtext of influence on the content and form of the film. The conclusions indicate that the use of philosophical and psychological analysis of films allows the teacher to encourage students to deep analytical thinking and develop emotional intelligence, since this process is accompanied by such analytical operations as selecting interesting material, preparing multimedia presentation and accompanying text, discussing the problem, and debating.
Keywords: philosophical and psychological analysis; interactive method; psychological constructivism; critical thinking; analytical skills; emotional intelligence